Insights into sources and atmospheric processing at two polluted urban locations in the Indo-Gangetic plains from stable carbon and nitrogen isotope ratios and polycyclic aromatic hydrocarbons in ambient PM2.5. (15th February 2022) - Singh, Gyanesh Kumar; Rajeev, Pradhi; Paul, Debajyoti; Gupta, Tarun
Abstract: Ambient PM2.5 samples collected from two heavily polluted locations (Kanpur and Prayagraj) in Indo-Gangetic plains during wintertime were analyzed for stable isotopes ( ẟ 13 C and ẟ 15 N), polycyclic aromatic hydrocarbons (PAHs), carbonaceous components, and ionic species. These data helped in understanding the aerosol composition, emission sources, and the associated atmospheric chemistry. Major contribution of high molecular weight (HMW) PAHs (4-ring, 5-ring, and 6-ring) to the total PAHs was observed at both the sampling sites. Organic carbon (OC) was a significant component of carbonaceous aerosols at both locations. In addition, OC/EC ratio (>2) revealed a dominant contribution from secondary organic carbon (SOC) during the sampling campaign. The contribution of SOC to total OC was much higher in Kanpur than in Prayagraj. A strong correlation between K + BB and OC observed for the two sites indicates a major influence of biomass burning. ẟ 13 C values of bulk PM2.5 samples at Prayagraj were slightly lower compared to Kanpur. ẟ 13 C and PAH isomeric ratios indicate significant contributions from biomass burning and petroleum combustion at both locations. Enhanced SOC formation appeared to control the ẟ 13 C at the Kanpur location, which may be due to the formation of secondary organic aerosol (SOA; 13 C-depleted) from volatile organic compounds (VOCs) derived from combustion-generated aerosols (biomass/fossil fuel). This study also reports the ambient ẟ 15 N of aerosols at the Prayagraj site. The correlation of ẟ 15 N with nitrogenous components WSON, NH4 + _N, and NO3 − _N suggest 15 N-depleted sources at the Prayagraj site. Like Kanpur, WSON and NH4 + _N also influenced the bulk ẟ 15 N values of Prayagraj aerosols. Graphical abstract: Image 1 Highlights: Biomass burning and petroleum combustion appear to be major sources of aerosols. Enhanced SOC formation appeared to control the ẟ 13 C at the Kanpur location. ẟ 15 N and nitrogenous species suggest 15 N-depleted sources at the Prayagraj site. WSON and NH4 + _N influenced the bulk ẟ 15 N values of Prayagraj aerosols.